Escola complementar de Caxias : histórias da primeira instituição pública para formação de professores na cidade de Caxias do Sul (1930-1961) - Bergozza, Roseli Maria (My University, 2014)
The present work aims at researching and analyzing the organization and installation of the first public official institution devoted to primary teachers´ formation in 1930 in Caxias do Sul, by that time named Escola Complementar de Caxias, and later renamed Escola Normal Duque de Caxias. The study relied on the possibility of having a look at the institution, through the inventory of the practices from both teachers and students who have experienced the school and have cooperated to the construction of the school culture. The individuals involved in the whole process are historically considered, since they are constituted by practices and discourses. The theoretical support is based on the postulates of the Cultural History and on the conceptual triad proposed by Roger Chartier: appropriation, representation and practice. The documental analysis has been done through the interpretation of the documents produced by the institution, the reports from the stewardship and also the files from Arquivo Histórico Municipal João Spadari Adami. The text is organized into three chapters: it starts with some points on the city of Caxias do Sul, taking historical aspects into consideration, since the arrival of the first immigrants until the creation and installation of the school in 1930 and contemplating the history of education in the city. After that, I examine the people involved in the schooling process, giving emphasis to the role of principals, teachers and students. Finally, it has been focused on the elements of school culture, mainly the practices related to knowledge and discourses implied in the schooling process. Initially, the school practices have demonstrated traits of the new school and medical discourses, and then, from 1939 on, they have indicated the strong influence of the nationalist discourse. The expansion and affirmation of the public school in the region has happened vigorously due to the empowerment and qualification on the teacher´s formation and, above all, the installation of Escola Complementar de Caxias as a turning point to teacher´s professionalization both in the city and the region, showing, this way, the feminization of the teaching
O presente trabalho tem como propósito pesquisar e analisar a organização e instalação da primeira instituição pública, de caráter oficial, para formação de professores primários, em 1930, na cidade de Caxias do Sul. Escola Complementar de Caxias, posteriormente denominada Escola Normal Duque de Caxias. O estudo assentou-se na possibilidade de produzir um olhar sobre a instituição, através do inventário das práticas produzidas e produtoras dos sujeitos que vivenciaram a mesma e contribuíram para a construção das culturas escolares. Os sujeitos envolvidos no processo escolar são historicamente (re)lembrados, visto que eles se constituíram nas práticas e nos discursos. Como referencial teórico, recorre-se aos postulados da História Cultural e à tríade conceitual proposta por Roger Chartier, apropriação, representação e prática. A análise documental se deu pela interpretação dos documentos produzidos pela instituição, pelos relatórios da Intendência e pelo acervo do Arquivo Histórico Municipal João Spadari Adami. O texto está organizado em três capítulos, iniciando com as considerações acerca da cidade de Caxias, abordando aspectos históricos, desde a chegada dos primeiros imigrantes até a criação e instalação da Escola em 1930, contemplando ainda a história da educação escolarizada na cidade. Na sequência, analiso os sujeitos envolvidos no processo escolar, enfatizando o papel dos diretores (as), professores (as), e alunos (as). E, por fim, focalizam-se elementos das culturas escolares, sobretudo as práticas permeadas pelos saberes e discursos implicados no processo escolar. As práticas escolares, inicialmente, denotam características dos discursos escolanovista e médico, a partir de 1939, indicam forte influência do discurso de cunho nacionalista. A expansão e afirmação da escola pública na região se deu com maior vigor a partir da crescente qualificação do processo de formação de professores, sobretudo com a instalação da Escola Complementar de Caxias como um marco significativo da profissionalização docente na cidade e na região evidenciando assim, a feminização do magistério.
Keywords: Educação; Escola complementar; Escola normal; Culturas escolares; Nacionalismo na educação; Feminização do magistério; Escola nova; Professores - Formação - Caxias do Sul (RS); Escolas públicas; Educação - História - Caxias do Sul (RS); Complementary school; Teaching school; School culture; Nationalism on education; Feminization on the teaching; New school; Training of Teachers - Caxias do Sul (Brazil); Public schools; Education history - Caxias do Sul (Brazil)